2008
DOI: 10.1016/j.chroma.2008.04.060
|View full text |Cite
|
Sign up to set email alerts
|

Doping control analysis of insulin and its analogues in equine plasma by liquid chromatography–tandem mass spectrometry

Abstract: Insulin administration can increase muscle glycogen by utilising hyperinsulinaemic clamps prior to sports events or during the recovery phases, and increase muscle size by its chalonic action to inhibit protein breakdown. In order to control insulin abuse in equine sports, a method to detect effectively the use of insulins in horses would be required. Besides the readily available human insulin and its synthetic analogues, structurally similar insulins from other species can also be used as doping agents. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…However, this assay consistently underestimates equine insulin concentrations when compared with LC-MS. 12 Although mammalian insulins demonstrate substantial homology, equine insulin does differ from porcine, human, and bovine insulin by 1-3 amino acids. 5 These substitutions may affect insulin binding due to different secondary, tertiary, or quaternary protein structure. 1,4 Depending on the amino acid sequence recognized by antibodies in different immunoassays, available assays may vary in detection of equine insulin.…”
Section: Discussionmentioning
confidence: 99%
“…However, this assay consistently underestimates equine insulin concentrations when compared with LC-MS. 12 Although mammalian insulins demonstrate substantial homology, equine insulin does differ from porcine, human, and bovine insulin by 1-3 amino acids. 5 These substitutions may affect insulin binding due to different secondary, tertiary, or quaternary protein structure. 1,4 Depending on the amino acid sequence recognized by antibodies in different immunoassays, available assays may vary in detection of equine insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Current methods for protein quantification by LC/MS have employed antibody-based purification through molecular recognition of target proteins and/or peptides in addition to immunodepletion of major background proteins [17,18,21]. Two-dimensional solid phase extractions have been used to reach low ng/mL levels and achieve precise and accurate results without the use of antibodies [27].…”
Section: Discussionmentioning
confidence: 99%
“…The drawbacks associated with this technique include expensive kits, possible imprecision, minimal volume applied, and minimal column life (<200 samples) [16]. Immunopurification of the target protein can also be accomplished and has also been shown to yield lower limits of detection [17][18][19][20][21]. However, the requirement for antibodies for immunopurification makes this technique less desirable.…”
Section: Introductionmentioning
confidence: 97%
“…IA purification of the protein target is useful for both native and therapeutic proteins. For example, Ho et al [37] reported the simultaneous detection of five exogenous insulin in equine plasma via IA purification LC-MS analysis. Lopez et al [38] demonstrated the feasibility of immunopurification of the parathyroid hormones and the analysis of the same by MALDI-TOF.…”
Section: Immunoaffinity Purificationmentioning
confidence: 99%